Service thinking the seven principles to discover innovative opportunities - Hastings, Hunter; Saperstein, Jeff.; ebrary, Inc. (New York Business Expert Press, 2014)
Business paradigm shifts are rare. However, the shift to a service-dominant economy and to service-dominant value creation genuinely merits such a designation, both on the surface through the lens of traditional economic measures and even more deeply and profoundly through the lens of Vargo and Lusch's Service-Dominant Logic (S-D Logic). Almost 80% of GDP in developed economies is attributable to services, and some economists regard products as merely the physical embodiment of service delivery. Yet today's business analysis, business management, business organization, business processes, and business education emerged from a manufacturing-dominant logic; the principles of service are often underserved and poorly understood. This results in lost opportunities for growth.
1. Service thinking will transform 21st century business -- 2. Co-creating service-experience value -- 3. Service systems: specialization plus integration -- 4. Designing organizations for specialization and integration: modular business architecture -- 5. Glo-Mo-So scalable platforms -- 6. Continuous improvement through learning: run-transform-innovate -- 7. Multisided metrics -- 8. Applying service thinking for innovation -- 9. The individualization of opportunity and your career -- Afterword -- Endorsements -- Notes -- References -- Index.
Dr. Tiffany Adelaine G. Tan (Recommending faculty) : Management Cluster
Includes bibliographical references (pages 129-132) and index.
Keywords: Customer services; Service industries; analytics; co-creation.; marketing; modularization; service science; service system; value